Potential use of indigenous medicinal weeds as grain protectants in hilly regions of North-East India - Devina, S; Haobijam, J W; Aquiny, B T M; Chandrakumar, S K; Ganeshkumar, D R; Deepa, T (Plant Science Today, 2026)
Seed beetles are widely prevalent and economically destructive storage pest that infest stored grains on a global scale. Apart from other climatic challenges, Northeast Indian farmers struggle with these pests, resulting in considerable losses in terms of both quantity and quality. The primary objective of this study was to identify environmentally sustainable, readily available and novel alternatives to synthetic insecticides for their management, in addition to neem. In this context, the effectiveness of 6 different indigenous medicinal weeds was studied against the storage beetle (Callosobruchus chinensis) and demonstrated through various experiments on its biological parameters, such as oviposition inhibition, adult mortality and adult emergence percentage, which also correlates with seed damage percentage. The results indicated that seeds treated with Calotropis exhibited the highest mean mortality, the lowest oviposition and the most seed damage, while Zanthoxylum emerged as the subsequent successful treatment, highlighting its first report of insecticidal properties against this storage pest. This was followed by Argemone, Ageratum and Eupatorium. Lantana leaf powder demonstrated the lowest adult mortality rate and highest grain damage; nevertheless, it may be utilised during periods when other plants are scarce. These findings indicate that utilising indigenous medicinal plants as grain protectants during storage can be a viable and environmentally safe alternative to chemicals, provided that they do not possess any potential toxicity risk to people and the grains are thoroughly washed after the treatment prior to consumption. This technique not only promotes sustainability but also preserves the use of native botanical resources, which may benefit local farmers. Further research and development are required to understand their chemical compositions completely and use them as valuable plants.